Toward a Genealogy of the Balkan Discourses on Race. Issue 6 (18th August 2018) - Bjelić, Dušan I.
Abstract : The ongoing racist reception of immigrants by post-communist states previously known to be class conscious, internationalist, and egalitarian naturally raises the question: how is racism possible in societies with no colonial or interracial experience? It is fair to state that the critical discourse on race barely exists and is historically and theoretically alien to postsocialist historiography on the grounds that Eastern Europe and the Balkans did not have and never were colonies. An attempt to engage the postsocialist presence with postcolonial analysis and to introduce race into the postsocialist context remains for the most part foreclosed by postsocialist historiographies. And yet every one of these postsocialist countries had racial laws during World War II and readily shipped Jews to concentration camps; as soon as real socialism collapsed, class consciousness morphed overnight into rabid nationalism coupled with racist practices. So, race must have always been – in some capacity – part of Eastern European, and particularly of Balkan, history. Informed primarily by Michel Foucault's genealogy of race discourses, I will interrogate the ways in which the Balkans instrumentalized class and ethnicity as race in the struggle over sovereign space. This essay examines the Balkans "racial formations" in relation to war, revolution, the science of eugenics, the serology of "blood type, " procreation, and the Marxist discourse on race. Rather than a "thing" of nature, the Balkan "race" is a "thing" of discourse.